Numerical investigations of low load diesel-methane dual fuel combustion at early diesel injection timings. (1st May 2022) - Jha, P.R.; Wijeyakulasuriya, S.; Krishnan, S.R.; Srinivasan, K.K.
Highlights: Methane addition delays onset of both low- and high-temperature heat release in dual fuel combustion. Methane trapped in crevices is a major source of unburned hydrocarbons at early injection timings. Local temperature stratification influences the formation of nitrogen oxide emissions. The extent of high reactivity fuel stratification significantly influences combustion evolution. Abstract: The present work focuses on the development and validation of a CFD simulation setup of diesel-methane dual fuel combustion in a single-cylinder research engine (SCRE). The validated setup is used to provide insight about dual fuel combustion at low-load operation. The computational campaign consisted of evaluating three different diesel injection timings of 310, 320, and 330 CAD at a methane percent energy substitution (PES) of 80%, 5.1 bar gross IMEP, 500 bar diesel injection pressure, and 1.5 bar manifold air pressure where 360 CAD corresponds to firing top dead center. The computational setup ability to capture combustion, performance, and emissions trends accurately is demonstrated by good agreement with experimental data. The validated setup is further utilized to provide insights into the nature of dual fuel combustion, particularly, the effect of methane on diesel autoignition. Analysis of the computational results showed that the onset of both low-temperature heat release and high-temperature heat release of n-dodecane (the chemical surrogate used for diesel) is delayed by the presence of methane in the system. For early diesel injection in a dual-fuel engine at low-load, initial high-temperature combustion arises from the burning of n-dodecane followed by methane combustion. Most of the methane present in the piston compression ring crevices, areas near the piston top and the liner, remained unreacted after combustion is done. The effect of diesel and methane fuel amount on engine performance at low-load was also explored.